THE ROLE OF DIGITAL TECHNOLOGIES IN THE INTELLECTUAL ACTIVITY OF THE BLIND (Web of Technology: Multidimensional Research Journal, 2025)
In recent decades, changes in Uzbekistan's humanitarian sphere have been marked by increased attention to the social integration of people with disabilities. The state's social policy is increasingly aimed at creating equal opportunities for such individuals to participate in society and engage in socially beneficial activities. One of the most important aspects of ensuring equal opportunities for visually impaired individuals is providing them with access to information and enabling active participation in social information exchange. The process of digitalization makes these issues even more relevant. In this regard, the widespread use of digital electronic resources, especially those designed to meet the needs of visually impaired individuals and digital technology requirements, is of particular importance. This study substantiates the use of digital educational resources and computer assistive technologies in the context of interaction with the information society. The findings can be applied in academic and corporate educational institutions. The developed approaches can be utilized by various groups of developers to create their own digital learning environments.